(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yu Y, Liu H, Xu Z, Yan P, Wu H, Wu L. 2024. Analysis of the difference in endophytic bacterial community structure between infected and non-infected rice plants with rice bakanae disease. Biodiversitas 25: 197-204. Rice bakanae disease, caused by the main pathogen Fusarium fujikuroi, is an important fungal disease that seriously threatens rice production. This study analyzed the effect of Fusarium fujikuroi on the community structure and diversity of endophytic bacteria in different rice tissues. The total DNA of different tissues, such as root, stem, and leaf, was extracted after artificial inoculation, and the bacterial 16SrRNA gene library was constructed. The high-throughput sequencing was used to analyze the biological information of bacterial community composition, diversity and function. The results showed that a total of 467841 effective sequences were obtained. Alpha diversity analysis showed that the diversity and richness of the endophytic bacterial community in infected plants were higher than in non-infected plants. At the phylum level, Cyanobacteria, Proteobacteria, Firmicutes, Acidobacteria, Bacteroidetes, Chloroflexi, and Actinobacteria were the dominant phyla. The infection of rice seedling bacteria causes changes in the abundance of endophytic bacteria in rice. Compared with non-infected plants, the abundance of Streptophyta and Acidovorax in the root decreased by 1.29 and 0.74%, respectively. The abundance of Geobacter, Devosia, Pleomorphomonas, and Herbaspirillum increased by 1.05, 1.55, 1.28, and 1.76%, while the abundance of Streptophyta in stem decreased by 7.83%. The abundance of Xanthomonas, Acidovorax, Pseudomonas and Sphingomonas increased by 1.55, 1.49, 1.11 and 1.15%, whereas the abundance of Streptophyta in the leaf decreased by 12.03%, Actinomycetales, Pseudomonas, Sphingomonas are significant biological differences between different tissues of infected and non-infected plants. The study provides a theoretical basis for the biological control of rice bakanae disease.